ROCK PROPERTIES SENSIVITITY IN HYDRAULIC FRACTURING APPLICATION FOR LOW PERMEABILITY SANDSTONE HPHT RESERVOIR - Putra - NIM 12213014 , Akbar
This study is an example of application of well stimulation using hydraulic fracture to overcome low permeability in the gas reservoir with high pressure high temperature well condition. Hydraulic fracture stimulation of the well is a method by using the compatible fracturing fluid and create cracks. The proppant is used to hold crack from closing, allowing fluid to flow from reservoir into the wellbore. Proppant and fracturing fluid are applied in sandstone to improve well productivity. For fracturing under High Pressure High Temperature (HPHT) condition, the proppant and fracturing fluid must be selected by considering its compatibility with reservoir condition. High temperature requires special fracturing fluid which can withstand up to 400 oF while in high pressure condition the proppant must be able to hold stress at 10,000 psi. This study was conducted using 3D fracturing software FracProPT2007. The software generated base case of the hydraulic application using required reservoir and well data. By changing the value of rock properties such as; Young Modulus and PoissonÃ‚Â’s Ratio, the software is also used to determine rock properties sensitivity toward fracture geometry in High Pressure High Temperature reservoir.